2013
DOI: 10.1177/1091581813504224
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Assessment of Heavy Straight Run Naphtha in a Repeated Dose/Reproductive Toxicity Screening Test

Abstract: Gasoline blending stocks (naphthas) are comprised of normal, iso-and cycloparaffins and aromatic hydrocarbons with carbon numbers ranging from C4 to C12. Heavy straight run naphtha (HSRN, CAS number 64741-41-9) was selected for toxicity screening because substances of this type contain relatively high levels (28%) of cycloparaffins by comparison to other naphtha streams and the data complement toxicity information on other gasoline blending streams. Rats were exposed by inhalation to wholly vaporized material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The thyroid, liver, and pituitary changes are characteristics of a consequence of hepatocellular induction as a result of enhanced hepatic metabolism. 29 As a side effect of hepatic induction, an increased liver metabolism of thyroid hormones T3 and T4 can occur. This subsequently leads to an enhanced thyroid gland production of these hormones, resulting in a negative feedback stimulation of TSH production.…”
Section: Parental Toxicitymentioning
confidence: 99%
“…The thyroid, liver, and pituitary changes are characteristics of a consequence of hepatocellular induction as a result of enhanced hepatic metabolism. 29 As a side effect of hepatic induction, an increased liver metabolism of thyroid hormones T3 and T4 can occur. This subsequently leads to an enhanced thyroid gland production of these hormones, resulting in a negative feedback stimulation of TSH production.…”
Section: Parental Toxicitymentioning
confidence: 99%
“…As no hazards were identified that differed from previously published results of either naphtha streams or formulated gasoline, it was concluded that the hazards of all naphthas fall within the range of substances tested and that further toxicological testing for hazard characterization is unnecessary. 51 Benzene, when present, must be taken into account and, in particular, the occupational exposure recommendations for benzene must be observed. Finally, with respect to risk assessment, it should be noted that naphthas may have relatively wide boiling ranges and that exposures are primarily to the more volatile C 4 -C 6 constituents.…”
Section: Characterization Of Toxicological Hazard Information For Majmentioning
confidence: 99%